A differential steering control with proportional controller for an autonomous mobile robot - Mohd Saifizi, Saidonr; Hazry, Desa, Dr.; Rudzuan, Md Noor (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/